Cycloyvoltammetry, ATR-IR of AlCl3/Amide and Thioamide DES and the Morphology of Deposited Aluminum at Variable Potential and Temperature - Hadi M. A. Abood (Journal of Global Pharma Technology, 2016)
Aluminium was successfully electrodeposited from mixtures of aluminium chloride with two amides and two thioamides. Structure identification by ATR-IR spectroscopy suggested the interaction of   (AlCl2+) species with oxygen, sulfur and nitrogen respectively which influence the cyclovoltammetry behavior of the mixtures. Morphology of electrodeposited aluminium from the protected mixtures by decan layer examined by SEM and EDX showed variable shapes and microsize due to the effect of  variable temperatures (30°C to 60°C) and potentials (-0.6V to -1.6V), this in part is related to mass transport limitation and coordinating ligands.   Keywords: DES, Electro-deposition, Aluminium, AlCl3-amide, AlCl3-thioamide.